Schottky barriers measurements through Arrhenius plots in gas sensors based on semiconductor films - Schipani, Federico (2012)
The oxygen adsorption effects on the Schottky barriers height measurements for thick films gas sensors prepared with undoped nanometric SnO2 particles were studied. From electrical measurements, the characteristics of the intergranular potential barriers developed at intergrains were deduced. It is shown that the determination of effective activation energies from conduction vs. 1/temperature curves is not generally a correct manner to estimate barrier heights. This is due to gas adsorption/desorption during the heating and cooling processes, the assumption of emission over the barrier as the dominant conduction mechanism, and the possible oxygen diffusion into or out of the grains.